Safety Factors of Oils Marketed in Iran and Applicable Strategies in Control of Food Derived Cardiovascular Diseases - Jamali, Ali; Moslemi, Masoumeh; Akramzadeh, Naeimeh; Khaneghah, Amin M.; Dadgarnejad, Manouchehr (Current Nutrition & Food Science, 2020)
Background: The proposed criteria for a healthy daily diet play a drastic role in the prevention of non-communicable disease. Several cases of acute and chronic diseases occurred due to the presence of toxic and unsafe agents in the body. Trans and some saturated fatty acids as an example of these unfavorable components, could pose some dangerous effects on human health such as cardiovascular disease. Objective: In the current study, health criteria were undertaken to evaluate the safety of collected edible oils samples from Iranian market, and then some of the approaches for elimination and control of arisen health concerns were discussed. Methods: Totally 18 edible oil samples including cooking oil (n=5), frying oil (n=9) and table margarine (n=4) were collected from Tehran local market and were analyzed in 2016. The fatty acid profile was determined by using gas chromatography equipped with a flame ionization detector. Furthermore, the stability of frying oil was also measured by the Rancimat method. Results: All samples contained the trans and saturated fats in concentrations lower than the maximum recommended values (1%, 2% and 4% of trans for cooking oils, frying oils and table margarines, and 30% and 48% of saturation in frying oils and table margarines, respectively). The frying oils demonstrated the desired stability against high temperatures. Optimization of stability was done mainly by the addition of palm oil to the formula in the past. However, based on the fact of the high saturation of palm oil and its carcinogenicity under uncontrolled consumption, a risk assessment conducted in Iran led to the limited import of palm oil. This approach resulted in the production of healthier alternatives in the country. Conclusion: The usage of applicable approaches such as inter-esterification, fractionation and blending by more stable oils fractions is suggested to achieve healthier products.
Keywords: oil